Wrong tooth extraction: an examination of 'Never Event' data. Issue 2 (February 2017) - Pemberton, M.N.; Ashley, M.P.; Saksena, A.; Dickson, S.
Abstract: The NHS in England has identified several adverse incidents that involve patients, including operations done at the wrong site, as "never" events. We examined published data from the period April 2012 to October 2015 and found that "wrong tooth/teeth removed" is the most common "wrong site" event, and accounted for between 20% and 25% of wrong site surgery never events, and 6% - 9% of all "never" events. All "wrong tooth/teeth removed" events seem to have been reported only by hospitals or Community Trusts. It is important to find out how these events are recorded and to find ways to prevent them.